(untitled) (Asian Journal of Medical and Biological Research, 2016)
The research work was conducted on 105 layer chicks with a view to determine the rate of distribution of neurotropic virulent Newcastle disease virus (NVNDV) in various organs following infection through natural (intranasal, intraocular and oral) and parenteral (intravenous, intramuscular and subcutaneous) routes of inoculation at different ages (7, 15 and 28 days of old). Each bird received a dose of 0.2 ml contained 300 ELD50 of reference NVNDV. The highest body temperature (?1080F) was recorded in the birds of almost all the experimental groups within 48 to 72 hours of PI. Appearance of clinical signs was observed earlier (48 to 72 hours of PI) in parenterally infected birds than those of inoculated through natural routes. The shortest duration (24-48 hours of PI) and longest duration (74-138 hours of PI) of death time were recorded in birds those inoculated through IV and oral routes of infection respectively. Isolation of NDV was positive from day 2 of PI and onward in all the groups with some minor variations in some cases. The CEF system was found more sensitive for the isolation of viruses compare to that of avian embryo. The highest HA titre of NDV was found in the brain tissue followed by lungs and kidney. Significantly (p<0.01) higher HA titre of NDV isolate was recorded in the birds of all the experimental groups inoculated through IV route. Following infection, the MDA titre decreased day by day in the birds with the increase of HA titres of NDV. Asian J. Med. Biol. Res. December 2015, 1(3): 526-536